Fiscal Decentralization and access to Social Services in Pakistan: Exploring the Role of Corruption - Karim, Yasir; Awan, Abdul Basit; Farwa, Umme; Khan, Amna (Pakistan Journal of Humanities and Social Sciences, 2023)
The present study looks at how accessibility to water and sanitation (social services) are affected by fiscal decentralization during the years 1980–2020 by incorporating the role of corruption in Pakistan using an ARDL Bounds testing approach. Two indicators, including revenue and expenditure decentralization, are employed to precisely capture the essence of fiscal decentralization. The Corruption Perception Index is used to quantify corruption. The empirical results indicate that decentralization of revenue and expenditures has a growing impact on social service access. The study offers proof that corruption not only impairs access to social services but also lessens the benefits of fiscal decentralization on that access. To achieve the desired effects of fiscal decentralization, the policy framework needs to take particular actions, such as increasing accountability and transparency to reduce corruption and enhance the quality of institutions.